Approaches to rational glucocorticoid therapy in the treatment of rheumatic diseases I. B. Bashkova, - I. B. Bashkova; I. V. Madyanov (Лечащий Врач, 2021)
The article presents the principles of rational glucocorticoid therapy in the treatment of rheumatic diseases. They are based on strict adherence to indications for the use of glucocorticoids, the choice of their method of administration, the prescription of the most optimal drug, selection of an effective dose mode, duration of treatment, dose reduction rates and timely cancellation of glucocorticoids in achieving acceptable results of treatment.